Autoimmune encephalitis associated with antibodies against the metabotropic glutamate receptor type 1: case report and review of the literature. (May 2019) - Christ, Monika; Müller, Torsten; Bien, Corinna; Hagen, Thomas; Naumann, Markus; Bayas, Antonios
Autoimmune encephalitis associated with antibodies against the metabotropic glutamate receptor type 1 is a rare autoimmune disease with only 18 cases being described in the literature so far. Most patients present with subacute cerebellar ataxia. In more than one third of cases a paraneoplastic aetiology has been suspected. Here we report a case of a 45-year-old man without known malignancy, who presented with progressive dysarthria and subsequently developed subacute cerebellar ataxia. Immunotherapy with glucocorticoids, i.v. immunoglobulins and rituximab improved clinical symptoms and resulted in a stable disease course up to the present. The article describes the clinical course of the patient with a follow-up-period of approximately 24 months and reviews the cases reported in the literature so far.